Increasing farmer´s digital agency and cocreation: the Solis experience in Brazil - Laurens, Violaine (2025)
Presented by Violaine Laurens, Solidaridad Latin America, at the “Increasing farmer’s digital agency for agroecology” webinar on 8 May 2025, an event of the Transformative Partnership Platform (TPP) for Agroecology and Agroecological TRANSITIONS Project (ATDT).